PERLINDUNGAN HUKUM TANAH ADAT SETELAH TERBITNYA PERATURAN PEMERINTAH MENGENAI BADAN BANK TANAH - Permadi, Iwan; Muttaqin, Irsyadul (Legal Standing : Jurnal Ilmu Hukum, 2024)
This article aims to analyze agrarian conflicts and legal protection of customary land after the establishment of the Government Regulation on the Land Bank Agency in Indonesia. The presence of the Land Bank has the potential for conflict of interest and recognition of customary land can be neglected under the pretext of stateization. This research uses normative research and is based on statutory and conceptual approaches. The results show that agrarian reform contained in the Land Bank study actually backs up agrarian reform itself in terms of land acquisition, because land can be obtained through the transfer of land ownership by the state. Therefore, within the framework of ius constutuendum, the Government needs to improve the Job Creation Law in the land sector and the Government Regulation on the Land Bank, in addition, the public can also conduct a Material Test on articles containing land stateization arrangements in the Job Creation Law and Government Regulations on the Land Bank to strengthen guarantees and fulfillment of the rights of indigenous land communities.